Divergent monetary policies and international dollar credit: Evidence from bank-level data - Dong He; Eric Wong; Kelvin Ho; Andrew Tsang (Asian Development Bank Institute (ADBI), 2017)
This paper uses a comprehensive and detailed bank-level data set to study how the divergence of central bank balance sheet policy in the US vis-à-vis the euro area and Japan affects the supply of international US dollar loans by global banks. Our empirical findings support the view that the contractionary effect of US monetary normalization on global dollar liquidity would be offset by an expansionary effect from a continued supply of US dollar loans by euro area and Japanese banks. The net effect, however, is crucially dependent on the stability of global foreign exchange markets and investor perceptions of the default risks of global banks. The analysis shows that US monetary policy shocks are one of the most important explanatory variables for the deviations from the covered interest rate parity (CIP) in the major foreign exchange (FX) markets. We also demonstrate a tail risk scenario of the contraction of the supply of international US dollar loans if and when the US monetary normalization coincides with a dislocation of the FX swap market and a rise of bank default risks. Our results are robust to alternative model specifications and different data sets.
Keywords: E44; E52; E58; E63; 330; Finance sector development; Japan